1980
DOI: 10.1017/s0033291700047310
|View full text |Cite
|
Sign up to set email alerts
|

The lifetime prevalence of mental disorders: estimation, uses and limitations

Abstract: SYNOPSISThe age-specific lifetime prevalence rate of a disease is the proportion of persons surviving to a given age who have experienced the disease at any time during their lives. This measure of morbidity has been used to report findings in many of the epidemiological surveys of mental disorders of the last 30 years. This paper presents a life-table method for estimating age-specific lifetime prevalence rates from incidence and mortality data. The method is applied to Monroe County, New York, case register … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1982
1982
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…The 132 core studies provided from one to 13 prevalence estimates per study. Four studies [59,120,169,224] reported prevalence only within narrow age strata without providing an overall rate. These studies were not included in the discrete core analyses.…”
Section: Resultsmentioning
confidence: 99%
“…The 132 core studies provided from one to 13 prevalence estimates per study. Four studies [59,120,169,224] reported prevalence only within narrow age strata without providing an overall rate. These studies were not included in the discrete core analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the low prevalence of 12-month MDD (.029) and lifetime MDD (.046), we report detailed results in online appendices e-Figures 1 and 2. We focus on past-year (vs. lifetime) MDD because within the context of a trial, the past-year measure captures MDD during a period that follows random assignment, preserving temporal order between exposure and outcome 31 . Moreover, results for past-year MDD have not been published within MTO.…”
Section: Design and Methodsmentioning
confidence: 99%
“…They depend not only on the limited reliability of present case finding and identifying techniques, but also on the distant memory of respondents’ (p. 92). This was echoed by Kramer et al (1980), who wrote that ‘Lifetime prevalence has been an exceptionally popular morbidity measure in epidemiological surveys of mental disorders. It is doubtful that this popularity is deserved’ (p. 429).…”
Section: Problems With Lifetime Prevalence As An Epidemiologic Parametermentioning
confidence: 99%
“…Kramer et al (1980) attempted to take mortality into account regarding lifetime prevalence, by using a life-table approach, and assuming various age-standardized mortality ratios for people with schizophrenia. Their results indicated that not taking mortality into account could lead to underestimates of lifetime prevalence at older ages.…”
Section: Possible Reasons For the Decline In Lifetime Prevalence Withmentioning
confidence: 99%